TWO NEW Aphelenchoides Fischer 1894 (Nematoda: Tylenchina) FROM MANIPUR, NORTH EAST INDIA - Loukrakpam Bina Chanu; Naorem Mohilal (BIOTROPIA, 2014)
Two new species of Aphelenchoides discovered from different localities of Manipur, North East India had been described in the present study. Aphelenchoides longistylus sp. nov. has a long stylet and four lateral lines which are gradually merged into two at the tail region. Aphelenchoides neominoris sp. nov. has a small body and short tail with a stylet length of 8.6 Âµm.